Menggali Potensi Bromo: Pengalaman Study Tour Fakultas Ilmu Komputer - Kanedi, Indra; Suci, Tiara Pramuni; Azzahra, Rupawan; Sari, Intan Mayang; Novrianto, Nanda (Universitas Dehasen Bengkulu, 2024)
This study describes the experience of a study tour conducted by the Faculty of Computer Science to the area of Mount Bromo, one of the famous tourist destinations in Indonesia. The aim of this study tour is to explore the tourism potential of Bromo's natural attractions and to gain deeper understanding of various aspects related to tourism development in the region. During the study tour, participants were given the opportunity to explore the beauty of Bromo's landscape, learn about the local culture, and interact with the local community. The results of this study tour are expected to provide valuable insights for the participants and contribute positively to the development of tourism potential in the Bromo area.